The urban underserved: attitudes towards gaining full access to electronic medical records - Dhanireddy, Shireesha (John Wiley and Sons Inc., 2012)
BACKGROUND: As the use of electronic medical records (EMRs) spreads, health‐care organizations are increasingly offering patients online access to their medical records. Studies evaluating patient attitudes towards viewing elements of their records through secure, electronic patient portals have generally not included medically underserved patients or those with HIV/AIDS. The goal of this study was to gain insight into such patients' attitudes towards online access to their medical records, including their doctors' visit notes. METHODS: Qualitative study of four focus groups with adult patients in general adult medicine and HIV clinics at a large county hospital. Transcripts were analysed for themes using an immersion/crystallization approach. RESULTS: Patients' baseline understanding of the health record was limited. Perceived benefits of online access were improved patient understanding of health and disease, convenience, empowerment and a stronger relationship with their provider. Concerns included threats to privacy, worries about being unable to understand their record, fear that the computer would replace direct provider contact and hesitancy about potential demands on a provider's time. Patients also recommended providing online visit reminders, links to credible health information and assistance for paying bills. CONCLUSION: Despite their initial lack of knowledge of the health record, focus group participants were overwhelmingly positive about the prospect of online access to medical records. However, they worried about potential loss of privacy and interference with the patient–provider relationship. As EMRs increasingly offer patients open access to their medical records, vulnerable patient groups will likely join others in desiring and adopting such change, but may need targeted support during times of transition.